Launch of a new journal on applied mathematics: Editorial review on Vol. 1 No. 1 - Zeeshan, Ahmed (Journal of AppliedMath, 2023)
The charm of applied mathematics resides in its powerful ability to resolve issues across a wide range of fields. Nowadays, all industries are currently experiencing growth, but in parallel, corresponding issues develop and wait to be resolved. Thus, applied mathematics begins to exert its effectiveness. We launched Journal of AppliedMath, a new international peer-reviewed journal focusing on the application of mathematical concepts and methods to various fields. Thanks to the contributions of all the authors and with the support of our Editorial Board and editorial staff, we successfully published the first issue of this journal.